Combining L-band Synthetic Aperture Radar backscatter and TanDEM-X canopy height for forest aboveground biomass estimation - Khati, Unmesh; Singh, Gulab (Frontiers in Forests and Global Change, 2022)
Synthetic Aperture Radar (SAR) backscatter based above-ground biomass (AGB) estimates are limited by the saturation of the backscatter-AGB curve. This work explores the potential of combining backscatter with Polarimetric SAR Interferometry (PolInSAR) estimated forest stand height for improved AGB estimation. The combined models utilizing L-band backscatter and TanDEM-X height are compared with established backscatter based models. The models are cross-validated - i.e. trained on one acquisition date and validated for other dates. It is observed that with the input of height, the combined models perform significantly better than backscatter based models with improvement in RMSE between 19% and 46%. The model utilizing HV-polarized backscatter and TanDEM-X PolInSAR height provides the best case AGB inversion with a R2 = 0.78 and RMSE of 27.1 Mg/ha or 22% of mean AGB. The results demonstrate the potential of synergistic combination of L-band PolSAR (backscatter) and X-band PolInSAR (height) products for AGB mapping over a tropical forest range in India.